Pengaruh Aplikasi Pupuk Kandang Sapi dan ZA terhadap Pertumbuhan serta Hasil Bawang Merah (Allium ascalonicum L.) pada Ultisol - Jaramel Hotmatuah Purba; Agnes Imelda Manurung; Bilter Sirait (Universitas Methodist Indonesia, 2025)
This study aimed to evaluate the effect of cattle manure and ZA fertilizer on the growth and yield of shallots (Allium ascalonicum L.) cultivated on Ultisol soil. The experiment was conducted in Medan Selayang, from January to April 2024, using a two-factor Randomized Block Design (RBD) with three levels of cattle manure and four levels of ZA fertilizer. Data were analyzed using analysis of variance followed by Duncan’s multiple range test. The results showed that cattle manure at a dose of 30 g per polybag significantly increased fresh bulb weight per plot, but had no significant effect on plant height, leaf number, other bulb yield parameters measured. ZA fertilizer significantly affected leaf number and stored bulb weight per plot, but showed no significant influence on other growth and yield traits. The interaction between cattle manure and ZA fertilizer showed no significant effect on all observed parameters.